Acute high-level exposure to WTC particles alters expression of genes associated with oxidative stress and immune function in the lung. (April 2015) - Cohen, Mitchell D.; Vaughan, Joshua M.; Garrett, Brittany; Prophete, Colette; Horton, Lori; Sisco, Maureen; Kodavanti, Urmila P.; Ward, William O.; Peltier, Richard E.; Zelikoff, Judith; Chen, Lung-chi
Abstract First responders (FR) present at Ground Zero in the first 72 h after the World Trade Center (WTC) collapsed have progressively exhibited significant respiratory injuries. The few toxicology studies performed to date evaluated effects from just fine (< 2.5 µm) WTC dusts; none examined health effects/toxicities from atmospheres bearing larger particle sizes, despite the fact the majority (> 96%) of dusts were > 10 µm and most FR likely entrained dusts by mouth breathing. Using a system that generated/delivered supercoarse (10–53 µm) WTC dusts to F344 rats (in a manner that mimicked FR exposures), this study sought to examine potential toxicities in the lungs. In this exploratory study, rats were exposed for 2 h to 100 mg WTC dust/m3 (while under isoflurane [ISO] anesthesia) or an air/ISO mixture; this dose conservatively modeled likely exposures by mouth-breathing FR facing ≈750–1000 mg WTC dust/m3. Lungs were harvested 2 h post-exposure and total RNA extracted for subsequent global gene expression analysis. Among the > 1000 genes affected by WTC dust (under ISO) or ISO alone, 166 were unique to the dust exposure. In many instances, genes maximally-induced by the WTC dust exposure (relative to in naïve rats) were unchanged/inhibited by ISO only; similarly, several genes maximally inhibited in WTC dust rats were largely induced/unchanged in rats that received ISO only. These outcomes reflect likely contrasting effects of ISO and the WTC dust on lung gene expression. Overall, the data show that lungs of rats exposed to WTC dust (under ISO) – after accounting for any impact from ISO alone – displayed increased expression of genes related to lung inflammation, oxidative stress, and cell cycle control, while several involved in anti-oxidant function were inhibited. These changes suggested acute inflammogenic effects and oxidative stress in the lungs of WTC dust-exposed rats. This study, thus, concludes that a single very high exposure to WTC dusts could potentially have adversely affected the respiratory system – in terms of early inflammatory and oxidative stress processes. As these changes were not compared with other types of dusts, the uniqueness of these WTC-mediated effects remains to be confirmed. It also still remains to be determined if these effects might have any relevance to chronic lung pathologies that became evident among FR who encountered the highest dust levels on September 11, 2001 and the 2 days thereafter. Ongoing studies using longer-range post-exposure analyses (up to 1-year or more) will help to determine if effects seen here on genes were acute, reversible, or persistent, and associated with corresponding histopathologic/biochemical changes in situ.